Ejection force in tubular injection moldings. Part I : effect of processing conditions - Pontes, A. J. (2004)
The development and manufacture of injection molds for high quality technical parts are complex tasks involving the knowledge of the injection molding process and the material changes induced by processing. In the case of some specific shapes (boxes, tubular fittings), the shrinkage is partially restricted by the mold. The molding shrinks against the core, inserts or pins. Thus, upon ejection, it will be necessary to overcome the frictional forces resulting from the shrinkage. The knowledge of the ejection force is a useful contribution to optimizing the design of molds with these features, and to guaranteeing the structural integrity of the moldings. A study on the effect of conditions on the ejection force required for deep tubular moldings is described for the cases of three common thermoplastic polymers. The studies were based on tubular moldings (60 mm diameter, 146 mm length, and 2 mm. thickness). The injection unit cell consisted of a 1 MN clamp force injection molding machine, thermal regulator, and material dryer. During processing, pressure, temperature and ejection force evolutions were recorded. The results show that the processing conditions noticeably influence the ejection force.